PERKEMBANGAN MINAT MASYARAKAT INDONESIA TERHADAP PERBANKAN SYARIAH - Devina Lutfa Dianti; Fauzatul Laily Nisa (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The Development of Indonesian Public Interest in Sharia Banking Shows an Increase, Mainly Due to the Increase in Public Awareness of Sharia Banking and the Advancements in Digital Technology Facilitating Access to Sharia Banking Services. This Study Found That Several Factors Influence People's Preference for Conventional Banks Over Sharia Banks, Such as Limited Understanding of Riba and Highly Competitive Market Conditions. However, Some People Choose Sharia Banks Due to the Sharia Values Present in Sharia Banks Being Considered Suitable, as Well as Minimal Administrative Fees and the Implementation of Profit-Sharing by Sharia Banks. The Conclusion of This Study Indicates That Public Interest in Sharia Banks Will Increase Until 2024, Supported by a More Diverse Range of Products, Advancements in Digital Services, and Increasing Public Awareness of Sharia Banking.